Ricardo Palma. The dissident and his mask - Forgues, Roland (2023)
Ricardo Palma is probably one of the most controversial Peruvian intellectuals of his time and probably also one of the most discussed writers since his first « Tradiciones» that broke with the scheme of the known literary genres were made known. His origins have been appreciated in different ways by the critics of his time and even more so by later critics based on ideological rather than literary considerations. The present article reveals the content of the unprejudiced readings of Ricardo Palma’s work made by the author in recent years and consigned in the recently published book Ricardo Palma Caballero en su burro. Negritude, dissidence and utopia. It is a book where it is attempted to explain from a meticulous and deep examination of the literary work of the Patriarch of the Peruvian Letters, of his abundant correspondence and of his active participation in the political contest, the committed content of his life and work with his dissimulated Afro-descendant origins, taking into account the racist environment of the time in which he had to live and write. Keywords: Traditions, negritude, dissidence, utopia, racism, identity, colonialism, slavery, Americanity, asnography.